Investigating the relationship between embryotoxic and genotoxic effects of benzo[alpha]pyrene, 17 alpha-ethinylestradiol and endosulfan on Crassostrea gigas embryos - Wessel, Nathalie; Rousseau, Sabrina; Caisey, Xavier; Quiniou, Francoise; Akcha, Farida (Aquatic Toxicology, 2007)
Genotoxicity biomarkers are widely measured in ecotoxicology as molecular toxic endpoints of major environmental pollutants. However, the long-term consequences of such damage still have to be elucidated. Some authors have suggested that the accumulation of unrepaired DNA lesions could explain the embryotoxicity of certain chemical pollutants. As embryotoxicity exerts a direct impact on the recruitment rate, genotoxicity could be closely related to disturbances of ecological concern and produce a possible impact upon population dynamics. The aim of the present work was to study the genotoxicity and the embryotoxicity of three relevant pollutants for oyster embryos: the polycyclic aromatic hydrocarbon, benzo[a]pyrene (BaP), the synthetic estrogenic hormone, 17 alpha-ethinylestradiol (EE2), and the organochlorine, pesticide, endosulfan (ES). For each substance, gamete fertilization was performed and embryo development followed in contaminated reference seawater. Following exposure, embryotoxicity was evaluated by calculating the percentage of abnormal D-larvae obtained at 20 h development. Genotoxicity was measured in parallel by conducting a comet assay on enzymatically dissociated cells of pre-shelled larvae (16 h development). The oxidized DNA base, 8-oxodGuo, was also measured by HPLC coupled to electrochemical detection. For each contaminant, the relationship between genotoxicity and embryotoxicity was then studied to check for the possible significance of genotoxicity in the population dynamics of marine bivalves from polluted areas. For BaP, embryotoxicity and DNA strand breakage were both observed from the lowest tested concentration of 0.2 nM. Induction of 8-oxodGuo was significant from 20 nM. Endosulfan exposure resulted in similar effects for oyster embryos but from higher concentrations and followed a concentration-dependent manner. Embryotoxicity and genotoxicity in terms of DNA strand breaks were observed for endosulfan from 300 and 150 nM, respectively. No change in 8-oxodGuo level was observed ...